Epigenetic regulation of adipose tissue expansion and adipogenesis by N6‐methyladenosine. (15th September 2020) - Wu, Ruifan; Wang, Xinxia
Summary: Obesity, defined as excessive fat accumulation, is strongly associated with metabolic diseases and cancer, and its prevalence is rising worldwide. Thus, understanding the molecular mechanism of adipogenesis is of fundamental significance. Epigenetic modifications play important roles in regulating adipogenesis. N 6 ‐methyladenosine (m 6 A), the most prevalent and abundant mRNA modification in eukaryotic cells, modulates multiple aspects of RNA metabolism, including mRNA stability, translation, splicing and export. Recent studies indicate that m 6 A methylation plays important roles in modulating gene expression and signal pathways in various physiologic processes and diseases. Notably, the significant function and regulatory mechanisms of m 6 A in adipogenesis are now emerging. In this review, we summarize recent studies that elucidate the vital roles of m 6 A modifications in regulating adipogenesis and adipose tissue expansion. Furthermore, we highlight the nutritional regulation of m 6 A methylation and adipogenesis, which may prove a novel therapeutic strategy to fight against obesity.